KAJIAN DAMPAK PEMINDAHAN IBU KOTA JAKARTA KE IBU KOTA NUSANTARA (IKN) DI KALIMANTAN TIMUR MENGGUNAKAN PENDEKATAN DPSIR - Dai Robby; Rakhmat Syukur Laia; Kevin Ewaldo (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
The relocation of the capital city from Jakarta to Nusantara (IKN) in East Kalimantan is a strategic move taken by the Indonesian government to address various issues faced by Jakarta, such as overpopulation, environmental challenges, and uneven development. This study employs the DPSIR (Driving Force-Pressure-State-Impact-Response) framework to analyze the driving forces, pressures, conditions, impacts, and responses related to the IKN relocation. The analysis reveals that government policy, high urbanization, and environmental problems in Jakarta are the main driving factors. Meanwhile, pressures related to land acquisition and agrarian conflicts in East Kalimantan present significant challenges. The study also finds that the impacts of this relocation have the potential to disadvantage indigenous communities, necessitating a human-centered and participatory policy response. By understanding these dynamics, it is hoped that the IKN relocation can be carried out more effectively and sustainably.